Agroclimatic Environment of Chickpea in Haryana - Rao, V Umamaheshwara; Singh, Diwan; Bishnoi, O P (Annals of Arid Zone, 2016)
The chickpea data on area, production and productivity in different districts of Haryana were collected for II crop seasons and analysed. The state of Haryana has been’ divided into six zones. The zone comprising of Hisar and Sirsa districts has high spread and high productivity, whereas, the other zone with AmbaIa district has low spread and low productivity, Winter rainfall and soil types were superimposed on these zones.